EFFECT OF TWO TAPERING METHODS ON INTERLEUKIN-6, CORTISOL AND PERFORMANCE IN ELITE MALE WRESTLER - Mehranpour, A.B.; Supaporn, S.; Hasani, S.H.; Witid, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : This study examined that effect of two types of tapering on interleukin-6(IL-6), cortisol and performance in elite male wrestler. Material : After 4 weeks of progressive training, wrestlers were randomly divided into three equal groups, 1-control group (N=10) continued performing progressive training for one week, 2-taper group 1 (N=10) continued with a 50% reduction in training volume for one week, 3-taper group 2 (N=10) continued with a 75% reduction in volume of training for one week .plasma blood IL-6 and cortisol levels were assayed from analysis obtained via standard ELISA. Also general strength of muscles was recorded as a performance test. All data were collected before and after progressive training and also after one week of tapering period. Results : There were significant reduction of IL-6 and cortisol levels in both tapering group comparing with control group (P≤0.05).There was significant reduction of IL-6 and cortisol levels among tapering 50% and tapering 75% after tapering period (P≤0.05). Also there was significant increase of general strength of muscles between tapering 75% and control group (P≤0.05). Conclusion : hence, one week tapering with 75% reduction in training volume after progressive training while the intensity kept high is effective strategy for reduction of IL-6, and cortisol levels and also increase performance. It seems that higher reduction of training volume when the intensity kept high is a good strategy for wrestler before main competition.